Возможности повышения эксплуатационных показателей турбоустановок для ТЭС и АЭС ОАО "Турбоатом" на основе математического моделирования - Шубенко, Александр Леонидович; Лыхвар, Н. В.; Швецов, Виктор Леонидович (Национальный технический университет "Харьковский политехнический институт", 2009)
The issues of transfer from standard methodic for remedial maintenance and replacement of TPP and NPP steam turbine plants (STP) to «on-condition» maintenance and repair of power generating equipment have been considered. Such transfer is impossible if STP diagnostic techniques and means are not put to use. We offer a new approach to solution of the problem of STP condition diagnosis by thermodynamic parameters which is based on application of comprehensive, flexible and adapted mathematical model for the purpose of determination of basic values of the diagnosed factors.
Keywords: энергетическое оборудование; расчетный ресурс; показатели надежности; диагностика ПТУ